A crystal plasticity FEM study on the deformation behaviours of bicrystals composites for potential use as load-bearing implants - Zhang, Jie; Wei, Jinhuan; Jiang, Xingmao; Wang, Chenyu; Wang, Hui; Wu, Guihua (Frontiers in Materials, 2025)
Metal matrix composites have shown great application potential in biomedical materials due to their excellent integrated properties. The deformation behaviours of metal matrix composites during fabricating and service are complicated. In this study, bicrystals processed by accumulative roll-bonding (ARB) were used as a representative case, and the deformation behaviours were investigated using crystal plasticity finite element method (CPFEM). The used three bicrystals were {112}<111>−{112}<111> (C-C), {112}<111>−{123}<634> (C-S), and {112}<111>−{001}<110> (C-RoCube), and the initial misorientation angles at the interfaces were 0°, 19.4°, and 35.3°, respectively. Pole figures, crystal rotation angles, and misorientation angles were used to characterize the texture evolution, and through-thickness shear strain γRD−ND and shear strain on slip systems were adopted to present the plastic deformation. The deformation behaviours in C-S were similar to C-C, due to the small difference in crystal orientations, while the comparison between C-C and C-RoCube shows distinct differences. The texture transition between C and RoCube was observed, and this textural transition altered the activated slip systems. The influence of interfaces on the deformation behaviours of neighbouring regions was strongly dependent on the interfacial misorientation angles.